“Fraught With All Sorts of Dangers:” Church, State, Politics, and the United Church of Canada Act, 1924 - Fair, Ross (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
Abstract“Fraught With All Sorts of Dangers” examines how the uniquely fragmented Dominion Parliament of 1924 handled Bill 47, An Act incorporating the United Church of Canada. It offers fresh insight into the issue of Church Union in Canada by exploring how a religiously and politically charged private member's bill forced federal politicians to consider the relationship between church and state in Canada, dredged up old divisions between English-speaking Protestants and French-speaking Roman Catholics, raised questions about the limits of federal and provincial jurisdictions and, at times, challenged parliamentary procedure. The paper explores the ways in which the Liberal government of William Lyon Mackenzie King attempted to avoid many of the controversies of the issue, ones which would later inflict political consequences upon Arthur Meighen and his opposition Conservative Party. Following public protests on Parliament Hill, the scale of which had never been witnessed, and following several lengthy, religiously infused debates in the House of Commons, Bill 47 was passed into law. Although the Church Union issue had raised many uncomfortable questions regarding the interaction of church and state, in the end, the interests of political expediency left most questions unresolved.